Pneumothorax in Giant Anteater (Myrmecophaga tridactyla) - Rodovalho Rodrigues, Lauriane; Bernardes Bizinoto, Lara; Garcia Lopes, Matheus; Neves Teodoro, Ananda; Linhares Sampaio, Renato; Rodrigues Rosado, Isabel; Gabellini Leonel Alves, Endrigo; Martin, Ian (Acta Scientiae Veterinariae, 2024)
Background: The giant anteater is a mammal that inhabits the entire national territory, but is found more frequently in the Brazilian cerrado. This mammal is threatened with extinction, a situation that may occur due to the occupation of areas intended for agriculture, predatory hunting, roadkill, injuries due to fires in its natural habitat and dog attacks. As a result of these situations, these animals can present several illnesses, such as fractures, pneumothorax or hemothorax, cranioencephalic trauma, and come to death. The present work aims to report the treatment of pneumothorax in a giant anteater (Myrmecophaga tridactyla), cared at the Uniube Veterinary Hospital, Uberaba, MG. Case: A free-living, female giant anteater with a body weight of 31.5 kg, referred by the fire department, was admitted to the emergency service at the Uniube Veterinary Hospital. The animal presented a poor body condition, apathy, muffled pulmonary auscultation, a temperature of 35.1ºC, and unmeasurable systolic blood pressure. It was also observed that the animal was dyspneic and had burns on the palmar and plantar surfaces of all 4 paws. Due to the severity of the animal’s respiratory condition, the thoracentesis procedure was performed as a means of diagnosis and it was observed that the animal had pneumothorax. Due to the lack of suction resistance and the worsening of the patient’s condition, a bilateral thoracic drain was inserted for air drainage. As an analgesic and sedative protocol, ketamine at a dose of 2 mg/kg IV, midazolam at a dose of 0.1 mg/kg IV and morphine 0.5 mg/kg IM were used. Antibiotic therapy was instituted for secondary pulmonary and dermatological conditions, using amoxicillin with potassium clavulanate at a dose of 25 mg/kg TID and enrofloxacin 10 mg/kg SID, both for 7 days. As a non-steroidal anti-inflammatory drug, meloxicam was administered at a dose of 0.1 mg/kg SID, for 3 days. The patient received fluid therapy for fluid maintenance and volume replacement based on Ringers lactate at a rate of 70mL/kg/day. After several emptying of the drains and patient’s stabilization, the animal was taken to the diagnostic imaging sector for radiological examinations. During the radiographic evaluation, the presence of radiolucent areas was observed in the ventrodorsal projection, suggesting accumulation of air in the pleural space, and in the lateral projections, dorsal displacement of the cardiac apex in relation to the sternum was observed, again suggesting the accumulation of air in the thoracic cavity. Even with all clinical-surgical and therapeutic interventions, the patient presented with acute pulmonary edema and died. The animal was referred to the pathology sector for necropsy, and the main necroscopic findings were pulmonary involvement, mainly on the left side, and pulmonary edema. Discussion: Due to the lack of evidence regarding the animal of this case having suffered any trauma and because it was a victim rescued from a forest fire, it is suggested that the cause of respiratory injuries, pneumothorax, pneumonia and pulmonary edema, may come from smoke inhalation. According to the literature, animals affected by forest fires can develop inhalation injuries due to contact with smoke or soot particles with the mucociliary epithelium. This contact leads to a defensive reaction by the respiratory system, with a decrease in ciliary movement and an increase in secretions due to inflammation. Although the animals condition evolved to death, the determined treatment with the placement of a bilateral vacuum thoracic drain had an effect and was essential for the animal’s survival in the first twenty-four hours. Keywords: pulmonary edema, lung disease, active suction drain, burned, wild. Título: Pneumotórax em Tamanduá-Bandeira (Myrmecophaga tridactyla) Descritores: edema pulmonar, pneumopatia, dreno de sucção ativa, queimado, selvagens.